Análise dos instrumentos urbanísticos no Município de Fortaleza e a verificação da aplicação dos recursos recebidos como contrapartida pela sua implementação e utilização - Ximenes, Renata Rodrigues (2024)
The general objective of this work is to analyze the urban planning instruments most used in the Municipality of Fortaleza and verify the application of the values received as a form of compensation. We sought to analyze the implementation of a win-win procedure, with the return to citizens of the benefits received by users of urban planning instruments. To this end, methodologies involving bibliographic and legislative analysis and documentary research were used, through descriptive and explanatory procedures. The main sources of data for this work were documents made available on the website of the Secretariat of Urbanism and Environment of the Municipality of Fortaleza – SEUMA, with normative foundations published in the Official Gazette of the Municipality of Fortaleza, as well as minutes of municipal council meetings, contracts and concession terms signed with the municipality. As a result, we saw the construction of public facilities, such as arenas, and the requalification of squares, parks and public places, in addition to the acquisition of materials for cultural centers. It is concluded, therefore, that there is an alignment between the values received and the use of urban planning instruments, through the measurement of financial resources for projects and public equipment in peripheral areas of the municipality of Fortaleza.